2015
DOI: 10.17721/2227-1481.5.3-10
|View full text |Cite
|
Sign up to set email alerts
|

Project VeSElkA: Vertical Stratification of Element Abundances in CP stars

Abstract: A new research project on spectral analysis which aims to characterize the vertical stratication of element abundances in stellar atmospheres of chemically peculiar (CP) stars, is discussed in detail. Some results on detection of vertical abundance stratication in several slowly rotating main sequence CP stars are presented and considered as an indicator of the eectiveness of the atomic diusion mechanism responsible for the observed peculiarities of chemical abundances. This study is carried out in the frame o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…Recently, a research project named VeSElkA was initiated by Khalack & LeBlanc (2015a to search for vertical stratification of element abundances in stellar atmospheres of main sequence CP stars. More than 50 slowly rotating objects with V sini < 40 km s −1 were selected from the catalogue of Ap, HgMn and Am stars of Renson & Manfroid (2009) and observed with the spectropalariometer ESPaDOnS at the Canada-France-Hawaii Telescope in the frame of this project.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a research project named VeSElkA was initiated by Khalack & LeBlanc (2015a to search for vertical stratification of element abundances in stellar atmospheres of main sequence CP stars. More than 50 slowly rotating objects with V sini < 40 km s −1 were selected from the catalogue of Ap, HgMn and Am stars of Renson & Manfroid (2009) and observed with the spectropalariometer ESPaDOnS at the Canada-France-Hawaii Telescope in the frame of this project.…”
Section: Introductionmentioning
confidence: 99%
“…This work was carried out within the framework of the MOBSTER Collaboration (David-Uraz et al, 2019;Sikora et al, 2019) and the VeSElkA project (Khalack & LeBlanc, 2015;Khalack et al, 2019a). In this study, we identified the targets that show photometric variability which may be attributed to stellar rotation and for which highresolution spectra and measurements of magnetic field are available.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been successfully employed to search for the signatures of vertical abundance stratification in the atmospheres Notes: a results for two separate spectra (see Table 1) of several BHB stars (Khalack et al 2008;Khalack et al 2010;LeBlanc et al 2010), one post-HB star (Khalack et al 2014), and several HgMn stars (Thiam et al 2010). A number of the upper main sequence CP stars observed in the frame of the VeSElkA project (Khalack & LeBlanc 2015a;Khalack & LeBlanc 2015b) have been studied using the aforementioned approach. The abundance analysis resulted in detection of indications of vertical stratification of iron abundance in stellar atmosphere of HD 95608 and HD 116235 (Khalack et al 2013;LeBlanc et al 2015) and of chromium abundance in stellar atmosphere of HD 22920 (Khalack & Poitras 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To search for the signatures and to study the vertical stratification of chemical species in the atmospheres of CP stars, we have initiated Project VeSElkA (Khalack & LeBlanc 2015a;Khalack & LeBlanc 2015b), which stands for Vertical Stratification of Element Abundances. Slowly rotating (Vsin i < 40 km s −1 ) CP stars of the upper main sequence were selected for our study using the catalogue of Ap, HgMn and Am stars of Renson & Manfroid (2009).…”
Section: Introductionmentioning
confidence: 99%